Analysis of the Implications of Learning Elementary Mathematics According to Jean Piaget's Theory - Jadidah, Ines Tasya; Annisah, Rizka; Melinda, Meta; Padiman, Padiman; Anggilin, Kaliana (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
The purpose of this study is to describe the concept of learning mathematics in elementary schools based on Jean Piaget's theory. The focus of the research is the implementation of mathematics education in elementary classes according to Jean Piaget's theory. The research method used in this study is qualitative research by collecting information or data through different literature, such as different reference books, articles and magazines related to the problem. in the hands of researchers. The object of this research is the implications of elementary school mathematics learning activities based on Jean Piaget's cognitive theory, so researchers collect information from books and literature sources about the influence of elementary school mathematics education based on Jean Piaget's cognitive theory. The results showed that the higher the elementary school class, the more perfect the cognitive abilities of children, cognitive abilities change according to the age stages of child development, besides that there are learning aids such as media and learning models that can facilitate students' understanding